Global emergence of Zika virus - Tjan, Richard (Universa Medicina, 2016)
Zika virus (ZIKV) belongs to the flaviviruses (family Flaviviridae), which includes dengue, yellow fever, West Nile, and Japanese encephalitis viruses. Zika virus was isolated in 1947, in the Zika forest near Kampala, Uganda, from one of the rhesus monkeys used as sentinel animals in a yellow fever research program.